Pengaruh Keputusan Pendanaan, Keputusan Investasi dan Kebijakan Dividen Terhadap Nilai Perusahaan pada Perusahaan yang Tergabung dalam Indeks LQ 45 yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2024 - Febria Handayani; Laila Wardani (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2026)
This study aims to analyze the effect of financing decisions, investment decisions, and dividend policy on firm value in companies included in the LQ45 index listed on the Indonesia Stock Exchange during the 2021–2024 period. Financing decisions are proxied by Debt to Equity Ratio (DER), investment decisions by Fixed Asset Ratio (FAR), and dividend policy by Dividend Payout Ratio (DPR). Firm value is measured using Price to Book Value (PBV). This research employs a quantitative approach using multiple linear regression analysis. The data are secondary data obtained from companies’ financial statements selected through purposive sampling. The results show that financing decisions, investment decisions, and dividend policy have a positive and significant effect on firm value.